A Theology of Suffering for Today’s Thai Society. - Boonyakiat, Satanun (Saengtham College Journal, 2022)
The reality of human suffering in Thailand demands a theology that is not just an academic exercise but can respond to different kinds of suffering appropriately. Also, it must be rooted in the Christian faith and learning from the Buddhist teachings, particularly the Four Noble Truths. Therefore, this article aims to present a theology of suffering that is relevant to today’s Thai society. This study will discuss three aspects of such theology: First, suffering is a complex reality. Therefore, suffering calls for a theology that specifically addresses different kinds of suffering and responds to them appropriately. Second, there are many interpretations of the causes of suffering in Christianity, but this article focuses on two interpretations that relate to the Buddhist teachings: suffering is the result of sin and suffering is a mystery. If the cause of suffering is sin, one must repent. If the cause of suffering remains a mystery, one should go through incomprehensible suffering by faith in God. Finally, proper attitudes and actions can empower sufferers and avert preventable suffering to a certain degree. However, only the redemptive work of God can bring suffering to a complete extinction. Therefore, human beings should believe in Jesus Christ and learn to participate in the suffering of Christ and suffering of other people.